KINERJA KOPERASI UNIT DESA (KUD) MINA DERMAGA KECAMATAN KALIANDA KABUPATEN LAMPUNG SELATAN BERDASARKAN PENDEKATAN TRIPARTITE - Fadilla Sari; Dyah Aring Hepiana Lestari; Suriaty Situmorang (Lampung University, 2021)
The purpose of this research is to analyze cooperative’s performance as a business entity, performance related to development, performance towards the interests of cooperative members, as well as economic and non-economic benefits received by members. This research was conducted at KUD Mina Dermaga using a case study method, the location was selected purposively with the consideration that the cooperative has not yet been ranked by researchers or local agencies. Responses stating that 30 people members. This research uses descriptive quantitative data analysis, customer satisfaction index analysis, and importance performance analysis. The results of this study indicate that the performance of business entities and performance related to the development of KUD Mina Dermaga are included in the qualified category. The performance of KUD Mina Dermaga in the interests of its members is of sufficient quality category. The economic benefits received by members are the difference in the cost of buying and selling services . The total annual average economic benefits received by KUD Mina Dermaga members are IDR 508,358.26. The non-economic benefits members on service performance and meeting the needs of members are in the high category (satisfied).Keyword : KUD, member satisfaction, performance